Sacral neuromodulation in children and adolescents with defecation disorders - Besendörfer, Manuel; Knorr, Christian; Kirchgatter, Annemarie; Müller, Hanna; Reis Wolfertstetter, Patricia; Matzel, Klaus; Diez, Sonja (Neurogastroenterology and Motility, 2024)
Background: Even if understanding of neuronal enteropathies, such as Hirschsprung's disease and functional constipation, has been improved, specialized therapies are still missing. Sacral neuromodulation (SNM) has been established in the treatment of defecation disorders in adults. The aim of the study was to investigate effects of SNM in children and adolescents with refractory symptoms of chronic constipation. Methods: A two-centered, prospective trial has been conducted between 2019 and 2022. SNM was applied continuously at individually set stimulation intensity. Evaluation of clinical outcomes was conducted at 3, 6, and 12 months after surgery based on the developed questionnaires and quality of life analysis (KINDLR). Primary outcome was assessed based on predefined variables of fecal incontinence and defecation frequency. Key Results: Fifteen patients enrolled in the study and underwent SNM (median age 8.0 years (range 4–17 years)): eight patients were diagnosed with Hirschsprung's disease (53%). Improvement of defecation frequency was seen in 8/15 participants (53%) and an improvement of fecal incontinence in 9/12 patients (75%). We observed stable outcome after 1 year of treatment. Surgical revision was necessary in one patient after electrode breakage. Urinary incontinence was observed as singular side effect of treatment in two patients (13%), which was manageable with the reduction of stimulation intensity. Conclusions: SNM shows promising clinical results in children and adolescents presenting with chronic constipation refractory to conservative therapy. Indications for patients with enteral neuropathies deserve further confirmation.
CRIS-Team Scopus Importer:2024-06-14
Keywords: enteral neuropathies; fecal incontinence; Hirschsprung's disease; sacral nerve stimulation; sacral neuromodulation